Chemical Analysis and Nutritional Assessment of Chicken Sempol in Local Markets: Analisis Kimia dan Penilaian Gizi Sempol Ayam di Pasar Lokal - Ina Nurtanti; Desna Ayu Wijayanti; Ardian Ozzy Wianto; Astari Ratnaduhita (Academia Open, 2023)
This study aims to evaluate the chemical composition and nutritional value of chicken sempol, a popular street food in Karanganyar Regency. Employing a survey method with quantitative descriptive analysis, three treatment groups (sellers A, B, and C) were assessed, each with four repetitions. Non-probability sampling was utilized. The findings demonstrate significant (P<0.05) variations in water content, protein content, carbohydrate content, and fat content among the chicken sempol samples. Chemical quality tests reveal water content at 48.54%, protein content at 9.64%, carbohydrate content at 47.20%, and fat content at 9.26%. Notably, chicken sempol from different vendors exhibited distinct chemical profiles, with the lowest fat content and highest carbohydrate content observed. The study concludes that chicken sempol with superior chemical quality is available on Jalan Lawu, underscoring the importance of such assessments for informing consumer choices and improving the overall nutritional landscape. Highlight: Comprehensive Evaluation: The study assesses the chemical composition and nutritional value of a popular street food, chicken sempol, within Karanganyar Regency using a survey-based quantitative descriptive analysis. Distinct Vendor Profiles: Significant variations in water, protein, carbohydrate, and fat content are observed among chicken sempol samples from different vendors, highlighting the need for vendor-specific assessments. Consumer Impact: The identification of chicken sempol with superior chemical quality on Jalan Lawu emphasizes the crucial role of such evaluations in guiding consumer choices and fostering improvements in the broader nutritional landscape. Keyword: Chicken Sempol, Nutritional Value, Chemical Composition, Street Food, Vendor Variation